Anti-inflammatory activity of d-pinitol possibly through inhibiting COX-2 enzyme: in vivo and in silico studies - Haque, Mst. Farjanamul; El-Nashar, Heba A. S.; Akbor, Md. Showkoth; Alfaifi, Mohammed; Bappi, Mehedi Hasan; Chowdhury, Afsana Kabir; Hossain, Muhammad Kamal; El-Shazly, Mohamed; Albayouk, Tala; Saleh, Na’il; Islam, Muhammad Torequl (Frontiers in Chemistry, 2024)
Introduction: D-pinitol, a naturally occurring inositol, has diverse biological activities like antioxidant, antimicrobial and anticancer activities. This study aimed to evaluate anti-inflammatory effect of d-pinitol in a chick model. Additionally, in silico studies were performed to evaluate the molecular interactions with cyclooxygenase-2 (COX-2). Methods: The tested groups received d-pinitol (12.5, 25, and 50 mg/kg) and the standard drugs celecoxib and ketoprofen (42 mg/kg) via oral gavage prior to formalin injection. Then, the number of licks was counted for the first 10 min, and the paw edema diameter was measured at 60, 90, and 120 min. Results and Discussion: The d-pinitol groups significantly (p < 0.05) reduced the number of paw licks and paw edema diameters, compared to negative control. When d-pinitol was combined with celecoxib, it reduced inflammatory parameters more effectively than the individual groups. The in silico study showed a promising binding capacity of d-pinitol with COX-2. Taken together, d-pinitol exerted anti-inflammatory effects in a dose-dependent manner, possibly through COX-2 interaction pathway.